The level of formation of professional and ethical competence of social teachers at the constituating stage of experiment - Ekaterina V. Beznosyuk (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки, 2019)
The article discusses the results of the ascertaining stage of an experimental study on the implementation of a model for the formation of professional and ethical competence of future social teachers in terms of training in a magistracy through a set of pedagogical conditions and a number of interconnected blocks (conceptual, organizational, technological and effective), as well as stages (preparatory, informational, technological, effective). In the context of this study, a substantial description of the ascertaining stage of an experimental study is described, diagnostic tools are provided that were used at this stage to determine the initial level of formation of special competencies (moral and axiological, moral and regulatory, moral and reflexive) that we identified as an effective part of professional development. ethical competence of social educators. The results of a diagnostic study of the levels of development of special competencies (moral and axiological, moral and regulatory, moral and reflexive) are presented.In the pedagogical experiment, 192 graduate students took part, which were divided into two groups: the control group (96 people) and the experimental group (96 people). The educational process in the control group was built in the traditional form, and in the experimental one it was aimed at introducing and testing the model of the formation of the professional and ethical competence of the social teacher.According to the results of an experimental study, both the experimental and control groups of the threshold and base level of professional ethical competence were established to dominate, which was the basis for the further implementation of the formative stage of the experiment to introduce pedagogical conditions aimed at the targeted development of undergraduates in the direction of training 44.03.02 "Psychological and pedagogical education" professional and ethical competence.